Research on sintering process and thermal conductivity of hybrid nanosilver solder paste based on molecular dynamics simulation. (November 2021) - Zhang, Zhongqing; Fu, Guicui; Wan, Bo; Su, Yutai; Jiang, Maogong
Abstract: Nanosilver solder paste has become one of the widely materials in the field of electronic packaging due to its excellent thermal conductivity and mechanical properties. This paper considers the rapid sintering technology characteristics, the sintering processes of the same diameters and hybrid diameters nanosilver solder paste are simulated from the microscope perspective based on the molecular dynamics simulation theory. By tracing the atoms' trajectories on the surface of the nanosilver particles, the dominant sintering mechanism is obtained. Then, the thermal conductivity of the sintered silver nanoparticles is calculated by the equilibrium molecular dynamics method. The simulation results show that the densest sintered silver layer with the highest thermal conductivity is obtained when the diameter ratio of hybrid nanosilver balls is around 1:1.4, which provides a technical reference for the future proportioning of nanosilver solder paste.